Investigation of changes in phase composition and tribological properties of 65G steel during electrolyte-plasma hardening - Rakhadilov, B.K.; Bayatanova, L.B.; Satbayeva, Z.A.; Kozhanova, R.S.; Yerbolatova, G.U.; Sakenova, R.Ye. (Karagandy University of the name of acad. E.A. Buketov, 2023)
This paper presents the results of studies of phase composition and tribological properties of 65G steel, before and after electrolytic-plasma hardening at different regimes. The technology of electrolyte-plasma hardening and laboratory installation for implementation of electrolyte-plasma hardening are described. It was found that after electroplasma hardening a modified layer consisting of α'-phase (martensite) and cementite M3C is formed. The developed technological process of hardening of a part made of 65G steel makes it possible to obtain layers on the surface of the part that provide an increase in wear resistance by 2 times and in resistance to abrasive wear by 1.7 times. The carried out investigations have shown perspective and expediency of application of the developed method to increase operational properties of parts working in conditions of friction and wear. This technology can be used to increase the service life of working elements of agricultural machinery.
Электролитті-плазмалық өңдеу кезінде 65Г болатының фазалық құрамы мен трибологиялық қасиеттерінің өзгеруін зерттеу
Исследование изменений фазового состава и трибологических свойств стали 65Г при электролитно-плазменном упрочнении
Keywords: hardening; phase composition; plasma-electrolyte hardening; wear resistance